Phonemic composition influences words’ aesthetic appeal and memorability - Theresa Matzinger; David Košić (PLoS ONE, 2025)
Positive emotional responses from pleasant experiences are known to enhance memory, yet the relationship between aesthetic appeal and linguistic memory remains understudied. To investigate this relationship, we designed pseudowords of varying appeal based on Crystal’s [1] phoneme rankings. Native English-speaking participants actively memorized these pseudowords and completed a free recall test, followed by two rounds of appeal ratings. Our results showed that, contrary to our predictions, pseudowords designed to be of intermediate appeal were rated as more appealing than those designed to be highly appealing or unappealing. Nevertheless, pseudowords designed to be highly appealing were recalled most frequently – even though participants themselves did not rate them as highly appealing. Also, overall, recalled words received higher appeal ratings from participants than non-recalled ones. These findings suggest that the phonemic and phonotactic composition of words may, indeed, have aesthetic value that correlates with words’ memorability. This encourages further exploration into how appeal interacts with other factors influencing linguistic cognition, including occurrence frequency or complexity. Our findings can inform applications in language learning, teaching, and marketing, while also offering theoretical contributions to our understanding of language evolution and change.